A new bisglycolamide substituted calix[4]arene-benzo-crown-6 for the selective removal of cesium ion: combined experimental and density functional theoretical investigation. Issue 52 (12th May 2016) - Kumar, Vikas; Sharma, J. N.; Achuthan, P. V.; Singh, D. K.; Ali, Sk. Musharaf
Abstract : Optimized structure of the complex of Cs + with CBCBGA at the B3LYP/SVP level of theory. Abstract : A new bisglycolamide substituted calix-benzo-crown-6 (CBCBGA) ionophore has been synthesized and characterized by using 1 H, 13 C NMR, ESI-MS and elemental analysis. Detailed investigations on the effect of various parameters such as the aqueous phase acidity, ionophore concentration and nitrate ion concentration on extraction of cesium have been carried out. The new ionophore is found to be highly selective for Cs over other metal ions present in the simulated high level liquid waste solution. The complexing ability of this novel ionophore towards Cs + and Na + metal ions was further complimented by predicting the structure, extraction free energy and fraction of charge transfer using the B3LYP density functional employing a split-valence plus polarization (SVP) basis set in conjunction with the conductor like screening model. The unusually high selectivity of CBCBGA for Cs + ion over Na + ion was established by the calculated value of difference in the free energy, ΔΔ G (Δ G ext, Cs + − Δ G ext, Na + ), −9.46 kcal mol −1, which is in good agreement with the experimentally determined value of −5.59 kcal mol −1 . The calculated values of ρ and ∇2 ρ at the bond critical point for the hydrated Na + ion are found to be reduced during complexation with the CBCBGA, whereas for the hydrated Cs + ion, though ρ remains same, the value of ∇2 ρ is increased which seems to play a decisive role in the higher selectivity to Cs + ion over Na + ion of CBCBGA. The new CBCBGA ionophore shows promise for the selective removal of Cs + ion over other metal ions present in the simulated high level liquid waste solution.